Investigation of multiwall carbon nanotube modified hydroxyapatite on human osteoblast cell line using iTRAQ proteomics technology - Xu, J. L. (2014)
Hydroxyapatite (HA) is a bioactive ceramic material with a chemical composition similar to natural bone, and carbon nano tubes (CNT) is able to enhance the brittle ceramic matrix without detrimental to the bioactivity. This study reported an attempt to use a commercially multiwalled CNT strengthen brittle hydroxyapatite bioceramics. Using iTRAQ-coupled 2D LCMS/ MS analysis, we report the first study of protein profile in osteoblasts from human osteoblastic cell line incubated separately on HA with and without strengthening multiwall CNT surfaces. Sixty proteins were identified and quantified simultaneously at the initial culturing stage of 3 days. The results were validated by Western blotting for selected proteins: Fetuin-A, Elongation factor II and Peroxiredoxin VI. Fetuin-A showed up-regulation, and Peroxiredoxin VI gave down-regulation in the osteoblasts cultured on HA based ceramic surfaces. Similar regulation was expressed by the protein of Elongation factor II on the phase pure HA surfaces as compared to the control group cultured on the polystyrene substrate. Relatively high EF 2 expression was detected on the phase the surfaces of CNT strengthen HA samples.